Features of the investigation of illegal felling - Oliynychuk, Roman (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The article considers illegal logging as a crime against the environment, analyzes the views of scientists on the categories related to the investigation of this offense, substantiates the importance of proper planning of law enforcement officers for successful detection of crimes against the environment committed by air pollution and when investigating air pollution.The author notes that the forest is extremely important as a natural resource, as well as a means of meeting human needs for wood and other forest products. In addition, this natural object is of no less value due to the impact on the climate, atmosphere, soil protection, water protection and other useful functions, as well as in health, recreation, cultural and aesthetic needs of society. However, due to declining forest areas and their degradation, soil erosion, declining biodiversity, increasing damage to wildlife habitats, degradation of watersheds, etc. are becoming more widespread, which ultimately leads to the destruction of quality of life and limited opportunities for sustainable development.The prompt and successful detection of crimes against the environment committed through illegal logging often depends on the proper planning of law enforcement officials at the initial stage of the investigation. After all, prompt and qualified actions at this stage make it possible to establish the consequences of criminal violations and record traces of the crime. But for a full, comprehensive and objective investigation of this crime, it is necessary to establish important circumstances by conducting various investigative actions, tactical operations.The author draws conclusions about a number of characteristic features of the investigation of illegal logging.First, this type of criminal encroachment on the environment is characterized by a high level of latency, which necessitates the use of specific tactics and techniques for their operational investigation. Secondly, an extremely important element of the investigation of illegal logging is the conduct of appropriate forensic examination, which is the most effective means of investigating cases of crimes related to illegal logging, provided that the requirements of criminal procedure law on the appointment and conducting this investigative action. Third, the study of documents related to the relevant criminal proceedings, the study and comparison of their data allows to form a sufficient evidence base. Fourth, the tactically correct interrogation of persons involved in the relevant criminal proceedings makes it possible to determine the full range of causes and circumstances of illegal logging, its consequences, persons responsible for compliance with forest protection rules, the degree of their guilt, the ability to avert illegal felling and its consequences.